A Comparative Study on the Compensations for the Occupational and Economic Damage of Road Accident Victims - Abu Mukho, Esraa Shukry Salman (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This study aims to shed light on the Palestinian Insurance Law No. (20) of 2005 and the Tunisian Insurance Journal No. (86) of 2005. It particularly investigates the extent to which the legislators achieve their goal of adopting a new system based on impartial regulations to ensure fair and equitable compensations to all those affected by road accidents. Methods: The study uses the comparative and analytical approach to examine the Palestinian and Tunisian insurance laws as well as the decisions of the Palestinian and Tunisian Courts of Cassation. Results: The study concludes that several articles of the Palestinian and Tunisian insurance laws support the insurer at the expense of the insured, particularity in relation to the compensations available for the occupational damage of road accident victims. Moreover, the study reveals that the Palestinian and Tunisian insurance laws in 2005 are not fair when it comes to compensating for the moral and financial damages upon the death of the insured in a road accident. Limiting the list of those who are entitled to compensations of this sort, whether in the Tunisian Insurance Journal or the Palestinian Insurance Law, is a clear violation of the legal goals of 2005. Conclusions: The legal goals of 2005 which aim to expand compensation coverage by ensuring fair compensation have not been fulfilled.